CURTAILING THE SECURITY CHALLENGES IN NIGERIA: LESSONS FROM THE QUR’ĀNIC STORY OF DHU AL-QARNAYN - Busayri, Sulyman Muhammad; Fahm, AbdulGafar Olawale (Jurnal Syariah, 2023)
The purpose of this paper is to examine the security challenge in contemporary Nigeria and to identify the lessons from the Qur’ānic story of Dhu al-Qarnayn as a model for addressing security issues in the country. This study is descriptive and qualitative. Selected examples of security issues in the Qurʾān and early Islam, the Qur’ānic references to security in Surah 18:83-101 and its connection to security challenges in Nigeria were reviewed, to identify a practical approach for curtailing security challenges to promote national development. Results show that Islam as a comprehensive religion, directly and indirectly, recommends various approaches towards mopping away the insecurity. The paper emphasizes that experience of Dhu al-Qarnayn as depicted in Q.18:83-101 is a sufficient idea in tackling the defacing occurrences of maiming, kidnapping, carting away of public properties, illegal protest, and the like.